Novel Insights Into the Hyperaccumulation Syndrome in Pycnandra (Sapotaceae) - Isnard, Sandrine; L’Huillier, Laurent; Paul, Adrian L. D.; Munzinger, Jérôme; Fogliani, Bruno; Echevarria, Guillaume; Erskine, Peter D.; Gei, Vidiro; Jaffré, Tanguy; van der Ent, Antony (Frontiers in Plant Science, 2020)
The discovery of nickel hyperaccumulation, in Pycnandra acuminata, was the start of a global quest in this fascinating phenomenon. Despite recent advances in the physiology and molecular genetics of hyperaccumulation, the mechanisms and tolerance of Ni accumulation in the most extreme example reported to date, P. acuminata, remains enigmatic. We conducted a hydroponic experiment to establish Ni tolerance levels and translocation patterns in roots and shoots of P. acuminata, and analyzed elemental partitioning to gain insights into Ni regulation. We combined a phylogeny and foliar Ni concentrations to assess the incidence of hyperaccumulation within the genus Pycnandra. Hydroponic dosing experiments revealed that P. acuminata can resist extreme Ni concentrations in solution (up to 3,000 µM), and dosing at 100 µM Ni was beneficial to growth. All plant parts were highly enriched in Ni, but the latex had extreme Ni concentrations (124,000 µg g−1). Hyperaccumulation evolved independently in only two subgenera and five species of the genus Pycnandra. The extremely high level of Ni tolerance is posited to derive from the unique properties of laticifers. The evolutionary and ecological significance of Ni hyperaccumulation in Pycnandra is discussed in light of these findings. We suggest that Ni-rich laticifers might be more widespread in the plant kingdom and that more investigation is warranted.